2019
DOI: 10.3389/fpsyg.2019.01629
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ Emotional Intelligence and Reactive Behaviors in Soccer Matches: Mediating Effects of Coach Efficacy Beliefs

Abstract: In the last 10 years, emotional intelligence (EI) has become a current issue of research in psychology, and there are indicators to consider that EI should be analyzed to help the coach to behave effectively during competitions. According to Boardley’s (2018) revised model of coaching efficacy, coaches’ EI is predictive of their efficacy beliefs, which, in turn, is predictive of coaching behavior. However, little is known about the mediating effects of coaching efficacy dimensions on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
1
4
0
1
Order By: Relevance
“…35 In addition, EI had a significant negative effect (−) on interruption intention. Research 36 showed that EI has a significant negative effect (−) on behavioral patterns, thus indirectly supporting this study. Although the lack of the direct validation of the relation between EI and interruption intention limits comparison and analysis in previous studies, this study suggests that EI is an antecedent to persistent participation in sports and thus reduces the desire of interruption intention.…”
Section: Discussionsupporting
confidence: 85%
“…35 In addition, EI had a significant negative effect (−) on interruption intention. Research 36 showed that EI has a significant negative effect (−) on behavioral patterns, thus indirectly supporting this study. Although the lack of the direct validation of the relation between EI and interruption intention limits comparison and analysis in previous studies, this study suggests that EI is an antecedent to persistent participation in sports and thus reduces the desire of interruption intention.…”
Section: Discussionsupporting
confidence: 85%
“…The current results were in disagreement with Brandes and Elvers (2017) who reported a decrease in physical load levels with the use of technical instructions during small-sided games, even if the RPE increased. These differences could be due to the coaches' behavior (Foulds et al, 2019), coach encouragement (Teques et al, 2019;Díaz-García et al, 2021), technical information processes (Trigueros et al, 2019), and players' satisfaction (García-Calvo et al, 2014). Another reason for the higher increased RPE in the technical instruction than the combined condition in set 2 may be due to improved passing scores and, therefore, more physical fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, a reatividade foi utilizada referente às informações emitidas em resposta ao comportamento dos atletas, levando em conta que poderia ser uma ação desejada ou um erro. Estudos realizados no contexto do futebol já aplicaram este instrumento e não precisaram fazer adaptações do instrumento original (Marques et al, 2015;Teques et al, 2019).…”
Section: Instrumentos De Observação Sistemática Utilizados No Futebol...unclassified